Celastrol improves endothelial function in diet-induced obesity mice via attenuating endoplasmic reticulum stress through the activation of AMPK pathway - Cheng Yu; Weihong Lin; Jing Yang; Qiong Jiang; Wenkun Liu; Hongjin Liu; Yong Lin; Litao Wang; Lei Chen; Yu Huang; Lianglong Chen (Molecular Medicine)
Abstract Background Diet-induced obesity (DIO) is a significant factor in endothelial dysfunction. Celastrol, a potent anti-inflammatory and anti-oxidative pentacyclic triterpene, has shown promise as a protective agent against cardiovascular disease. However, the specific protective effects and mechanisms of celastrol in preventing endothelial dysfunction in diet-induced obesity are not yet fully understood. Methods and results In this study, eight-week-old C57BL/6 mice were fed a normal or high-fat diet and treated with or without celastrol for 8 weeks. We measured acetylcholine-induced endothelium-dependent relaxation (EDR) in the aortae using a wire myograph. The results revealed that EDR was impaired in DIO mice, along with decreased AMPK phosphorylation, increased endoplasmic reticulum (ER) stress, and reactive oxygen species (ROS) in the aortae. These effects were reversed by celastrol treatment. Celastrol also reversed tunicamycin-induced ER stress, decreased nitric oxide (NO) production, and impaired EDR in mouse aortae. The protective effects of celastrol were negated by co-treatment with an AMPK inhibitor (Compound C). Furthermore, in AMPKα deficient mice, the beneficial effects of celastrol on EDR were significantly reduced. Conclusions These findings suggest that celastrol improves endothelial function by inhibiting ER stress and increasing NO production through the activation of the AMPK pathway in DIO mice. Graphical Abstract The schematic diagram illustrates the mechanism by which celastrol ameliorates endothelial-dependent vasodilatation in diet-induced obesity mice. Celastrol activates the AMPK signaling pathway, thereby suppressing endoplasmic reticulum (ER) stress, inflammation, and reactive oxygen species (ROS) generation, which collectively enhance endothelial-dependent vasodilatation in diet-induced obesity mice.